RELIGIOUS EXISTENTIALISM IN CONTEMPORARY ISLAMIC DISCOURSE (STUDY OF SHARI'ATI'S THOUGHT) - Irwandi Bayu (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Humans are rational beings (Hayawān an-Nāthiq), with this potential, humans are able to become unique creatures with all their creativity. However, in expressing the unique values ​​possessed by humans, space for freedom is needed. So that with the availability of this space for freedom, humans are able to become creatures of existence. The study of individual freedom has attracted a lot of attention from Muslim and Western philosophers and has formed a famous variant of the discourse of thought with the term existentialism. The existentialism school of philosophy is a school of thought that considers that humans are unique individual subjects and cannot be understood in a closed and final sense, because each individual has initiative, initiative, free will, and creativity. Therefore, this article will examine the concept of religious existentialism offered by Ali tools used qualitative research methods, the study research library (library research) and theoretical content analysis (content analysis). The results of this study indicate that first, the definition of religious existentialism according to Ali Shari'ati is that humans are creatures who always exist, actively create themselves, act, become and change well, less or more than their previous state. In the process of becoming, man always moves towards the ideal stage of perfection, namely God. Second, the characteristics of Shariati's religious existentialism, he said that humans are two-dimensional creatures, namely: the basyariyah dimension and the insāniyah dimension. Besyar is a creature who simply are, but man is a creature that became, and only the values insaniyah capable of maximizing the potential of the divine so that man bears the title of Caliph of Allah on earth. To hone the potential insāniyah to God, Ali offered three conditions that must be met, namely: self-awareness, free will and creativity.